Indigenous Peoples and Local Communities Participation provisions in Negotiations on Conservation of Marine Areas Beyond National Jurisdiction - Radovich, Violeta Soledad (2023)
The objective of this chapter is to analyze indigenous and local communities (IPLCs) participation provisions in the Draft Agreement of an international legally binding instrument under the United Nations Convention on the Law of the Sea (UNCLOS) on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (BBNJ) to discuss whether they will lead to sustainability on the high seas.The efficacy of these provisions will be studied by checking whether they comply with legal criteria proposed to evaluate participation in environmental matters to achieve democracy.Provisions related to participation in the Aarhus Convention (AC) and the Water Framework Directive (WFD) will also be analyzed to decide if they may serve as a model for the BBNJ Agreement. Finally, decisions of Human Rights Courts and Committees referring to participation in sustainability issues will be scrutinized to evaluate what synergies they may provide.Conclusions show that IPLCs shall be granted the status of stakeholders in EIAs and shall be included as members of the Scientific and Technical Body in the BBJN provisions. Moreover, a reference to IPLCs free, prior and informed consent (FPIC) in EIAs shall be included in the Draft.